IDENTIFIKASI CEMARAN LOGAM Pb DAN Cd PADA KANGKUNG YANG DITANAM DI DAERAH KOTA DENPASAR - Mulyani, Sri; Triani, I.G.A Lani; Sujana E.N, Arief (Bumi Lestari; Vol 12 No 2 (2012), 2012)
The aimed of the research to identify the contamination of Pb and Cd on water spinach (Ipomeasp) planted at Denpasar. Sample population are 41 places area planted of water spinach, atKecamatan Denpasar Selatan 10 places , Denpasar Utara 10 places, Denpasar Timur 13 placesand Denpasar Barat 8 places. Sample has taken from 40% population, 13 areas planted of waterspinach at Denpasar. From Kecamatan Denpasar Barat 3 samples, Kecamatan Denpasar Timur3 samples, Kecamatan Denpasar Selatan 3 samples and 4 samples from Kecamatan DenpasarTimur. Samples taken 1-1.5 kg every area in the morning and identification of Pb and Cd areusing Kohar et. al., method and analyzed with Atomic Absorbsion Spectrophotometer (AAS). The result showed that no contamination of Pb on water spinach planted at Denpasar. Waterspinach has contamination Cd 0-0,00682 mg/kg. The water spinach which planted at KecamatanDenpasar Barat has lowest contamination of Cd, water spinach planted at Denpasar areproper to be consumed.
Keywords: water spinach; Denpasar; Pb and Cd